Role of strategic management for employee engagement and skill development for start-ups. Issue 1 (19th October 2020) - Kulkarni, Praveen; Mutkekar, Rohit; Ingalagi, Sanjeev
Abstract : Purpose: Start-ups are the new avenues for innovation and employment. Strategic management is critical for employee engagement and skill development of start-ups. This study aims to understand the impact of strategic management on employee engagement and skill development. Design/methodology/approach: The study attempts to identify principal factors of strategic management influencing employee engagement and skill development. Structural equation modeling has been used to understand effects of the study. Findings: The study results have shown the challenges concerning employee skill development and reflected on importance of the employee engagement programmes for the growth of the human resource in the start-ups. Research limitations/implications: The study has confined to strategic management for employee engagement and skill development. However, studies related to challenges encountered by start-ups in the specific areas of marketing, operations and finance, etc. would provide more detailed impact on the growth of start-ups. Practical implications: This study provides an insight into strategic management for employee engagement and skill development. The results would provide directions for improving strategy management from the perspective of employee engagement and skill development. Social implications: The study on start-ups provides a direction to the owners of start-ups to understand the importance of strategic management and human resource management for building strong enterprising which can provide employment opportunity for the youth of the nation and improve the society at large. Originality/value: This paper is an attempt to provide directions for managing challenges from the perspective of employees' engagement and skill development, which is essential for growth and sustainability in the future.